Verification of a theory of planned behavior model of medication adherence in Korean adults: focused on moderating effects of optimistic or present bias - Kyung Hyun Suh (BMC, 2021)
Abstract Background To prevent or recover from a disease, the prescriptions for medications must be correct, and the patient must comply with the medication's instructions. Therefore, this study verified the theory of planned behavior (TPB) model to predict medication adherence among Korean adults and examined the role of optimistic or present bias in that model. Methods The participants were 357 Korean male and female adults whose ages ranged from 18 to 76 (M = 41.53, SD = 9.89). Their medication adherence was measured with the Morisky Green Levine Scale. The study examined TPB factors with modified items related to medication adherence and optimistic bias with items developed based on the concept and on previous studies. Results An alternative TPB model, including a direct path from attitude to behavior, a direct path from the perceived behavioral control to the behavior, and an insignificant path from behavioral intention to behavior, was validated for Korean adults' medication adherence. This model was found to be moderated by optimistic or present bias. Conclusions The findings of this study should provide useful information for future research and for medical or health professionals who wish to improve the medication adherence of their patients.